The neutrophil-to-lymphocyte ratio independently predicts all-cause mortality in non-dialysis chronic kidney disease patients with preserved red cell distribution width: A retrospective cohort study - Yunkyeong Hwang; Janghyun Jo; Suyeon Han; Hwajin Park; Yu Ah Hong; Yoon-Kyung Chang; Dae Eun Choi (PLoS ONE, 2026)
Background The neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR), inflammatory indices derived from routine complete blood counts, and red cell distribution width (RDW) have been proposed as prognostic markers in chronic kidney disease (CKD). However, whether the inflammatory ratios retain independent prognostic value once erythrocyte homeostasis is considered, and whether their performance varies across the spectrum of erythrocyte heterogeneity captured by RDW, remains uncertain. Methods This retrospective cohort study included 2,654 adults with non-dialysis CKD followed at a single tertiary center between 2015 and 2022. Optimal biomarker cut-off values were determined by receiver operating characteristic analysis based on 3-year all-cause mortality. Associations of RDW, NLR, and PLR with dialysis-free survival and overall survival were assessed using Kaplan–Meier analysis and multivariable Cox proportional hazards models adjusted for age, sex, kidney function, comorbidities, and nutritional and metabolic parameters. RDW-stratified analyses and formal interaction testing were performed to to determine whether NLR retains independent prognostic value within RDW-defined subgroups. Parallel analyses restricted to patients with eGFR < 60 mL/min/1.73 m 2 were performed as a sensitivity analysis and reported as supplementary material. Results During a median follow-up of 2,413 days, 451 patients (17.0%) initiated dialysis and 239 (9.0%) died. In multivariable Cox analyses of the whole cohort, NLR did not retain an independent association with either dialysis initiation (HR 1.03, 95% CI 0.84–1.26; p = 0.771) or all-cause mortality (HR 1.23, 95% CI 0.92–1.64; p = 0.162). However, a statistically significant RDW × NLR interaction was observed for overall survival (p for interaction = 0.006): NLR was independently associated with mortality in the low RDW subgroup (HR 2.07, 95% CI 1.25–3.45; p = 0.006) but not in the high RDW subgroup (HR 0.88, 95% CI 0.62–1.26; p = 0.494). PLR did not retain independent prognostic value in any analysis, whereas RDW remained the only marker independently associated with all-cause mortality in the overall multivariable model (HR 1.72, 95% CI 1.31–2.26; p < 0.001). Fine-Gray competing-risks models yielded virtually identical estimates, and findings were consistent in the eGFR < 60 mL/min/1.73 m 2 subgroup. Conclusions In patients with non-dialysis CKD, NLR independently predicts all-cause mortality specifically in patients with preserved RDW, but loses incremental prognostic information once RDW is already elevated. These findings argue against the uncritical use of NLR as a universal prognostic marker in CKD and support an RDW-stratified, outcome-specific framework for applying inflammatory ratios in routine risk stratification.